A Dual-Band Zero-Index Metamaterial Superstrate for Concurrent Antenna Gain Enhancement at 2.4 and 3.5 GHz. Issue 4 (4th July 2022) - Haider, Zain; Khan, Muhammad U.; Cheema, Hammad M.
ABSTRACT: The classical printed monopole antenna exhibits wideband operation with low gain and an omnidirectional radiation pattern. In order to boost the gain of the antenna at two frequency bands, a novel dual-band zero-index metamaterial (ZIM) based on both electric and magnetic resonance is developed. The printed monopole is also backed by a metallic ground plane for unidirectional radiation pattern towards boreside. The presented unit cell is comprised of two Schurig split-ring resonators nested together in such an arrangement that it leads to a zero refractive index at two distinct frequencies. Using the proposed design methodology, a ZIM is designed operating at 2.4 and 3.5 GHz. To substantiate the improvement in gain, the proposed design is fabricated and used with a cavity-backed printed monopole antenna. The metamaterial superstrate increases the measured realized gain of the printed monopole antenna by 3.2 dB at 3.5 GHz and by 2.5 dB at 2.4 GHz, in agreement with simulations.